Boron and nitrogen co-doped ordered microporous carbons with high surface areas. Issue 100 (1st December 2017) - Castro-Muñiz, Alberto; Nishihara, Hirotomo; Hirota, Tetsuya; Ohwada, Mao; Li, Li-Xiang; Tsuda, Tetsuya; Kuwabata, Susumu; Maruyama, Jun; Kyotani, Takashi
Abstract : Boron and nitrogen co-doped ordered microporous carbons with high surface areas are obtained by using NaY zeolite as a hard template and an ionic liquid, 1-ethyl-3-methylimidazolium tetracyanoborate (EMIT), as a BN source. Abstract : Boron and nitrogen co-doped ordered microporous carbons with high surface areas are obtained by using NaY zeolite as a hard template and an ionic liquid, 1-ethyl-3-methylimidazolium tetracyanoborate (EMIT), as a BN source. An acetylene-gas supply during a pyrolysis is effective to avoid the unfavourable reaction of zeolite and EMIT.